나선형 부유 고분자 여재의 Coalescence 특성을 이용한 비점오염원 저감시설의 유수분리특성 연구 - 강성원(Sung Won Kang); 김석구(Seog Ku Kim); 김영임(Young Im Kim); 윤상린(Sang Leen Yun); 김수해(Soo Hae Kim); 김미경(Mee Kyung Kim) (Daehan hwan'gyeong gonghag hoeji, 2007)
Non-point source control system which had been designed only for oil-water separation in the fields of oil refinery and garage was upgraded in this research for the removal of runoff pollutants in impervious urban area. Pollutants including oil from driveway and bridge were eliminated by two types of pathway in the system. One is the coalescence mechanism that the oil droplets in the runoff come into contact with each other in the spiral buoyant media surface and form larger coalesced droplets of oil that are carried upstream to the oil layer. The other is the precipitation that solids in runoff were settled by gravity in the system. In this research, coalescing characteristics of oil and water separation were investigated through image analyses, and efficiencies of the non-point source control system were evaluated using dust in driveway and waste engine oil. Media made of high density and high molecular weight polyethylene was indeterminate helical shape and had sleek surface by analysing SEM photographs and BET. Surface area and specific gravity of media which were measured directly were 1,428 $mm^2$ and 45.3 $kg/m^3$ respectively. From the image analyses of the oil droplets photographs which were taken by using microscope, it was proved clearly that the coalescence was the main pathway in the removal of oil from the runoff. Finally, the performances of the non-point source control system filled up with the media were suspended solid $86.6\sim95.2%$, $COD_{Cr}$, $87.3\sim95.4%$, n-Hexane extractable materials $71.8\sim94.8%$ respectively. 본 연구에서 개발한 시스템은 기존에 사용되던 유수분리기를 유류가 혼입되어 발생하는 도로, 교량 등의 도시 불투수면 비점 오염저감장치로 업그레이드한 것으로서 유적입자가 coalescence 원리에 의하여 고밀도 고분자 폴리에틸렌 소재를 사용하여 제작된 메디아의 표면과 공간 사이를 타고 이동하면서 합체되어 유적의 크기가 증가한 후 부상하여 제거되는 기전과 SS 성분의 고형물이 침전에 의해 제거되는 원리를 이용한 도시 비점오염저감시설이다. 따라서 본 연구에서는 coalescence 기전을 통해 유수분리가 일어나는 나선형 고분자 여재의 유수분리 특성을 image analysis를 통해 규명하였으며 또한 도로노면 먼지와 폐엔진오일을 이용하여 비점오염원 저감시설에 유입되는 폐수를 모사하여 비점오염원 저감시설의 유수분리 성능을 실험하였다. 연구에 사용된 여재는 부정형의 투명한 나선형 구조를 갖고 있으며, SEM 사진 및 BET 측정 결과 매끄러운 표면 특성을 나타내고 있다. 직접 측정 방법으로 여재의 표면적을 측정한 결과, 여재 1립당 표면적은 1,428 $mm^2$으로 나타났으며, 단위당 중량은 45.3 $kg/m^3$으로 조사되었다. 또한 폐수 내 기름 입자의 액적크기를 현미경으로 촬영하여 이미지 분석을 수행한 결과, 메디아를 통한 폐수내 기름성분의 제거가 coalescence에 의해 일어나고 있음을 증명하였다. 마지막으로 나선형 부유 메디아를 적용한 비점오염저감시설의 성능평가 결과, 유량에 따라서 부유성 고형물은 $86.6\sim95.2%$, $COD_{Cr}$, $87.3\sim95.4%$, n-Hexane 추출물 $71.8\sim94.8%$의 제거효율을 나타내어 본 장치의 처리성능은 기존의 비점오염원 저감시설의 처리대상물질인 유기물과 부유물질 뿐만 아니라 유류의 제거에도 효과적인 것으로 평가되었다.